ALDH1A1 effect on Yan Yellow Cattle preadipocyte differentiation. Issue 2 (1st April 2021) - Hu, Zhongchang; Wu, Jian; Qin, Lihong; Jin, Haiguo; Lv, Yang; Zhang, Ran; Xiao, Cheng; Cao, Yang; Zhao, Yumin
Abstract: Aldehyde dehydrogenase 1A1 ( ALDH1A1 ) is a cytosolic enzyme that mainly catalyzes the oxidation of acetaldehyde into acetic acid and participates in the regulation of differentiation and gene expression in fat cell growth and development. However, the physiological role of ALDH1A1 in the formation of fat cell precursors in the Yan Yellow Cattle is still not clear. Herein, we investigated the specific regulation of the gene encoding for ALDH1A1 during the differentiation process of the adipocyte cells of the Yan Yellow Cattle by interfering or overexpressing the ALDH1A1 gene. As a result, we found that the mRNA expression levels of ALDH1A1 were significantly increased during the formation of progenitor cells. In addition, the expression levels of the Lipoprotein lipase (LPL ) and transcription factors ( PPARγ, C/EBPα ) were also significantly increased. ALDH1A1 gene overexpression and RNA interfering promoted and inhibited respectively the lipid accumulation and triglyceride production in mature adipocytes, and the expression of the LPL and transcription factors ( PPARγ, C/EBPα ). The changes in the protein expression levels of ALDH1A1 and adipogenic factors were in accord with the changes observed in the mRNA levels. In conclusion, our results indicate that ALDH1A1 plays an important regulatory role in the differentiation of preadipocyte cells.